High Performance Liquid Chromatographic Estimation of Gefitinib in Pharmaceutical Dosage Forms - Gowri Sankar, D.; Rajeswari, A.; Nagesh Babu, A.; Vanisha Devi, K.; Vamsi Krishna, M. (Asian Journal of Chemistry, 2010)
A reversed phase high performance liquid chromatographic method has been described for the estimation of gefitinib in its pharmaceutical formulations using C-18 column. The mobile phase consisted of pH 6.5 buffer (prepared by dissolving 1.5 g of potassium di-hydrogen phosphate in 550 mL of milli Q water (0.02 M) and adjusted the pH to 6.5 with triethylamine) and acetonitrile HPLC grade (Merck) in the ratio of 55:45 (v/v). The detection was carried out at 220 nm and the linearity was found to be in the range of 10-60 μg/mL. The method is simple, precise, specific, less time consuming and accurate for the estimation of gefitinib in pharmaceutical dosage forms.